2022
DOI: 10.1590/0103-8478cr20210041
|View full text |Cite
|
Sign up to set email alerts
|

Eurytrema coelomaticum infection: correlation between parasite burden and impairment of pancreatic exocrine enzyme secretion

Abstract: Eurytrema coelomaticum is a trematode reported in the pancreatic ducts of ruminants. It is conjectured that may cause disorders in the pancreas, as well as digestive and metabolic processes dependent on them. This study, determined if there is an impairment of exocrine pancreatic function, and correlated it with parasite burden. Pancreas, blood, and fecal samples were collected from 119 bovines at a abattoir. Stool samples were subjected to the gelatin and x-ray film digestion tests (to detect the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…In the definitive host infection, the metacercariae released from the cysts in the duodenum migrate to the pancreas through the accessory ducts and are distributed in the pancreatic ducts (Ilha et al, 2005). We found parasites both in the pancreatic ducts and duodenum, possibly related to the type of migration of Eurytrema and the degree of parasitism, since most studies have only reported the occurrence of the parasites in pancreatic ducts and occasionally biliary ducts (Surian et al, 2022). However, Bassani et al (2006) and Schwertz et al (2015) reported the occurrence in the duodenum was rare.…”
Section: Discussionmentioning
confidence: 69%
“…In the definitive host infection, the metacercariae released from the cysts in the duodenum migrate to the pancreas through the accessory ducts and are distributed in the pancreatic ducts (Ilha et al, 2005). We found parasites both in the pancreatic ducts and duodenum, possibly related to the type of migration of Eurytrema and the degree of parasitism, since most studies have only reported the occurrence of the parasites in pancreatic ducts and occasionally biliary ducts (Surian et al, 2022). However, Bassani et al (2006) and Schwertz et al (2015) reported the occurrence in the duodenum was rare.…”
Section: Discussionmentioning
confidence: 69%
“…In this scenario, some genera of greater importance and prevalence of gastrointestinal parasitic nematodes in cattle raised in tropical countries stand out, such as Cooperia, Haemonchus, and Oesophagostomum. The species Dictyocaulus viviparus is important in the parasitism of the lungs of these animals [1] along with the trematodes, whose species of importance in cattle are: Fasciola hepatica and Eurytrema coelomaticum, which are liver and pancreatic duct parasites of cattle, respectively [2,3].…”
Section: Introductionmentioning
confidence: 99%